RUTHVEN, Ian. and CHOWDHURY, G.G. (eds) Cultural Heritage Information Access and Management. London: Facet. 2015. 253 pages. ISBN 978-1-85604-930-6. £64.95. (2016) - Ravenwood, Clare
No abstract available